Preparation method of super-wear-resistant high-hardness nano titanium ceramic coating

By combining homemade silicone resin and filler, combined with the treatment of modified epoxy resin and carbon nanotubes, a high-hardness and ultra-wear-resistant coating is formed, which solves the wear and paint removal of metal substrate coatings and achieves high hardness and Wear resistance.

CN119177084AInactive Publication Date: 2024-12-24纪晓明
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411300411.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-08-02
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing metal base coatings are prone to wear and depaint after long-term use, and the uneven dispersion of titanium ceramic fillers leads to uneven surfaces of the coating, affecting wear resistance.

Method used

The homemade silicone resin and homemade filler are used to form a three-dimensional composite structure and silicon-oxygen bond connection through the treatment of modified epoxy resin and carbon nanotubes. Combined with ionic nitriding treatment, the paint's peel resistance and wear resistance are improved.

Benefits of technology

It realizes super wear-resistant and high hardness coatings on the surface of metal substrates, enhances the density and wear resistance of the coating, and significantly improves peel resistance and wear resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a super-wear-resistant high-hardness nano titanium ceramic coating, and relates to the technical field of coatings. According to the invention, the epoxy resin is modified by using 4-hydroxycrotonic acid and phosphorus pentoxide, and then the modified epoxy resin reacts with an organic silicon resin matrix, so that the stripping resistance of the coating is improved; then, the organic silicon resin matrix is further modified by n-propyl alcohol, so that the stripping resistance of the coating is improved, and the coating has relatively good compatibility with a self-made coating; the preparation method comprises the following steps: acidifying carbon nanotubes, adsorbing cerium ions by using the acidified carbon nanotubes, precipitating to form layered hydroxides, intercalating butyl titanate into the layered hydroxides, heating twice to form titanium porcelain to obtain a self-made filler which is of a three-dimensional composite structure and can be arranged in a resin matrix in an overlapping manner to improve the wear resistance of the coating, and carrying out ion nitriding treatment to effectively improve the wear resistance of the coating. The coating prepared by the invention has the effects of wear resistance and stripping resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a method for preparing a super wear-resistant and high-hardness nano titanium ceramic coating. Background Art

[0002] Metal substrates such as aluminum alloys are widely used in aerospace equipment, airports, subways, and architectural decoration due to their unique mechanical properties, lightness, and beauty. Usually, in order to improve the hardness and wear resistance of the material, it is necessary to apply a coating protection treatment to the metal substrate before use. Resin, titanium ceramics, and other fillers are often mixed to improve the hardness of the coating. In addition, due to long-term use, the paint film is susceptible to wear and paint peeling. Titanium ceramics and other fillers are prone to stacking due to uneven dispersion, resulting in an uneven coating surface. The coating surface is not well integrated with the resin matrix, which in turn exacerbates the wear of the coating.

[0003] Since silicone resin has a higher bond energy in its silicon-oxygen bond, it has higher thermal oxidation stability and heat resistance and is superior to general organic resins. However, its adhesion to the substrate is poor. After one year or even half a year of use, the paint film will fall off significantly, which limits its application to a certain extent. Epoxy resin contains many hydroxyl and ether bonds, which can greatly improve the adhesion of the coating, but it has poor compatibility with silicone resin and it is difficult to play its role in improving the performance of the coating. Summary of the invention

[0004] The purpose of the present invention is to provide a super wear-resistant and high-hardness nano titanium ceramic coating and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a super wear-resistant and high-hardness nano titanium ceramic coating, comprising a homemade silicone resin, a homemade filler, a diluent 660A, triethylenetetramine, and DMP-30. The super wear-resistant and high-hardness nano titanium ceramic coating is prepared by the following method: after the homemade silicone resin and the homemade filler are stirred and mixed, the diluent 660A is added, the mixture is heated in a water bath to a predetermined temperature, hydrogen and nitrogen are introduced, the temperature is continued to rise, vacuum insulation is performed for a period of time, and then triethylenetetramine and DMP-30 are added.

[0006] Furthermore, the homemade silicone resin is prepared from modified epoxy resin, 3-chloropropyltriethoxysilane, diethoxydichlorosilane, decamethylcyclopentasiloxane, 2,4,6,8,10-cyclopentasiloxane, tetramethyldihydrodisiloxane, 1,1,1-triethyl-3,3-dimethyldisiloxane, and n-propanol.

[0007] Furthermore, the modified epoxy resin is prepared from 4-hydroxycrotonic acid, epoxy resin E-51 and phosphorus pentoxide.

[0008] Furthermore, the self-made filler is prepared by the following method: treating carbon nanotubes with nitric acid to obtain pretreated carbon nanotubes; placing the pretreated carbon nanotubes in deionized water, ultrasonically dispersing, adding cerium nitrate hexahydrate, sodium sulfate, and hexamethylenetetramine, heating to a predetermined temperature in an oil bath under nitrogen protection, stirring for reaction, filtering, rinsing, and drying to obtain composite carbon nanotubes; then placing the pretreated carbon nanotubes in butyl titanate, ultrasonically treating, reacting at high temperature for a period of time, heating and heating, keeping the temperature for a period of time, and then cooling and keeping the temperature.

[0009] Furthermore, a method for preparing a super wear-resistant and high-hardness nano titanium ceramic coating comprises the following preparation steps: (1) The resin matrix was heated to 89-95°C, and modified epoxy resin, KP220, and ethyl acetate were added in a mass ratio of 1:0.0007:7-1:0.001:16. The mass ratio of modified epoxy resin to resin matrix was 0.4:1-0.8:1. After stirring at 150-200 rpm for 1-3 hours, the mixture was reacted for 9-18 hours under a nitrogen atmosphere, and then the temperature was lowered to 20-30°C. 0.9-2.0 times the mass of n-propanol of the resin matrix was added, and the mixture was reacted for 5-10 hours. The mixture was washed with deionized water until the pH of the solution was 6-7, and then distilled at 300-400 rpm and 77-85°C for 3-6 hours to obtain a self-made silicone resin. (2) Mix the homemade silicone resin and homemade filler in a mass ratio of 1:1.0~1:1.5, stir at 200~300 rpm for 3~7 hours, add 0.006~0.01 times the mass of the homemade silicone resin as diluent 660A, heat in a water bath to 46~59°C, introduce hydrogen and nitrogen, raise the temperature to 220~242°C, keep warm at a vacuum degree of 30~70Pa for 7~12 hours, add 0.01~0.03 times the mass of the homemade silicone resin as triethylenetetramine, 0.002~0.005 times the mass of the homemade silicone resin as DMP-30, stir evenly, and obtain an ultra-wear-resistant and high-hardness nano-titanium ceramic coating.

[0010] Furthermore, the preparation method of the modified epoxy resin in step (1) is as follows: at 86-96° C., epoxy resin E-51, 4-hydroxycrotonic acid, N,N-diethylbenzylamine, p-hydroxyanisole, and anhydrous ethanol are reacted at a mass ratio of 1:0.9:0.006:0.0005:0.06-1:1.4:0.01:0.001:0.3, at 150-250 rpm for 40-66 min, then cooled to 30-40° C., phosphorus pentoxide (0.6-1.0 times the mass of epoxy resin E-51) is added, and distilled at 72-89° C. and 200-300 rpm for 2-5 h to obtain the modified epoxy resin.

[0011] Furthermore, the preparation method of the resin matrix in step (1) is as follows: 3-chloropropyltriethoxysilane, diethoxydichlorosilane, decamethylcyclopentasiloxane, 2,4,6,8,10-cyclopentasiloxane, toluene, and zeolite molecular sieve are mixed in a mass ratio of 1:0.3:0.4:0.5:13:0.001-1:0.8:0.7:1:22:0.003, stirred evenly, placed in an oil bath at 67-75°C, and an ethanol aqueous solution of 4-11 times the mass of 3-chloropropyltriethoxysilane is added. The mass ratio of anhydrous ethanol and deionized water is 1:1. After reacting for 2 to 5 hours, tetramethyldihydrogen disiloxane and 1,1,1-triethyl-3,3-dimethyldisiloxane are added in a mass ratio of 1:0.6 to 1:1.4. The mass ratio of tetramethyldihydrogen disiloxane and 3-chloropropyltriethoxysilane is 0.2:1 to 0.6:1. After reacting for 1.5 to 3 hours, filter, separate layers, distill at 143 to 153°C and 400 to 500 mmHg for 4 to 9 hours, and then bake at 190 to 220°C for 20 to 36 minutes.

[0012] Furthermore, the preparation method of the self-made filler in step (2) is: A. Place the pretreated carbon nanotubes in deionized water 180 to 250 times the mass of the pretreated carbon nanotubes, and perform ultrasound at 25 to 35 kHz for 10 to 26 minutes. Then, add cerium nitrate hexahydrate, sodium sulfate, and hexamethylenetetramine in a mass ratio of 1:0.08:0.1 to 1:0.2:0.2. The mass ratio of cerium nitrate hexahydrate to pretreated carbon nanotubes is 0.7:1 to 0.9:1. Heat to 95 to 108°C in an oil bath under nitrogen protection. Stir at 100 to 130 rpm for 16 to 22 hours, filter, rinse with deionized water and anhydrous ethanol for 3 to 7 minutes, and dry at 60 to 70°C for 8 to 12 hours to obtain composite carbon nanotubes. B. Place the composite carbon nanotubes in butyl titanate which is 5 to 8 times the mass of the composite carbon nanotubes, and subject them to ultrasound at 25 to 35 kHz for 4 to 7 hours. After reacting at 200 to 220°C for 18 to 22 hours, heat the mixture to 600 to 630°C and keep the mixture for 5 to 8 hours. Then, cool the mixture to 322 to 367°C and keep the mixture for 6 to 9 hours. Then, filter the mixture, wash it with deionized water for 6 to 8 times, and dry it at 60 to 70°C for 3 to 5 hours to obtain the homemade filler.

[0013] Furthermore, the preparation method of the pretreated carbon nanotubes in step A is: placing the carbon nanotubes in 68% nitric acid with a mass fraction of 25 to 36 times the mass of the carbon nanotubes, ultrasonicating at 25 to 35 kHz for 24 to 36 minutes, stirring at 60 to 80 rpm for 3 to 7 hours, adding deionized water until the solution pH is 6 to 7, filtering, and drying at 68 to 80°C for 6 to 11 hours.

[0014] Furthermore, in step (2), the flow ratio of hydrogen to nitrogen is 3:1, and the total flow rate of hydrogen and nitrogen is 150 mm 3 / s.

[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The invention utilizes homemade organic silicon resin and homemade filler to obtain coating, which can be used on the surface of metal substrate to achieve the effects of anti-peeling and super wear resistance.

[0016] Firstly, the present invention uses 4-hydroxycrotonic acid to perform a ring-opening reaction on an epoxy resin, and the hydroxyl group of the epoxy resin reacts with phosphorus pentoxide to form a phosphate group, thereby obtaining a modified epoxy resin; then, 3-chloropropyltriethoxysilane, diethoxydichlorosilane, decamethylcyclopentasiloxane and 2,4,6,8,10-cyclopentasiloxane are used as reaction monomers, and tetramethyldihydrodisiloxane and 1,1,1-triethyl-3,3-dimethyldisiloxane are used as end caps to obtain a resin matrix; then, the silicon-hydrogen bonds of the resin matrix react with the double bonds of the modified epoxy resin in a reverse addition reaction, the high viscosity of the epoxy resin can improve the peeling resistance of the coating, and the phosphorus hydroxyl group of the phosphate group can form a strong chelating effect with the surface of the metal substrate, and is connected in the form of a covalent bond, thereby improving the peeling resistance of the coating; then, the hydroxyl group of n-propanol reacts with the chloride ion, and is grafted into the molecular chain of the self-made organic silicone resin, and can be bridged with the surface of the metal substrate by a silane bond, thereby improving the peeling resistance of the coating.

[0017] Secondly, the carbon nanotubes are first acidified to make the surface have carboxyl groups, and the end caps are opened. Then the carboxyl groups adsorb cerium ions, precipitate as nucleation points, and continue to grow to form layered rare earth hydroxides. Then, butyl titanate is intercalated into the layered rare earth hydroxides, and the first heating is performed to crystallize and form titanium dioxide. Then, the second heating is performed to form titanium porcelain. The carbon nanotubes, layered rare earth hydroxides and titanium porcelain are interlocked with each other to form a three-dimensional composite structure, which is tightly stacked and can be overlapped and arranged in a resin matrix, so that tiny bubbles, cracks and molecular cavities inside the resin are divided from each other, thereby forming a dense coating structure, which plays the role of a wear-resistant skeleton and improves the wear resistance of the coating. In addition, the homemade silicone resin and the homemade filler are connected by silicon-oxygen bonds to improve the density, thereby enhancing the wear resistance of the coating. After the homemade silicone resin and the homemade filler are mixed, ion nitriding treatment is performed to refine the grains while forming a lubricating layer on the surface of the homemade filler, which effectively improves the wear resistance of the coating. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the ultra-wear-resistant and high-hardness nano titanium ceramic coatings prepared in the following examples are as follows: The embodiment and the comparative example were coated on the surface of the metal substrate to the same thickness, and the super wear resistance and anti-peeling effect tests were performed; Super wear resistance: Using HT-1000 friction and wear tester, the normal load is 20N, the friction time is 120min, the rotation speed is 400r / min, the friction radius is 4mm, and the grinding ball is a silicon nitride ceramic ball with a diameter of 5mm. The samples are cleaned with ultrasonic alcohol before and after wear, and dried, weighed 3 times, and the average value is taken to calculate the wear amount; Peel resistance: Refer to GB / T 13448 to test adhesion level.

[0020] Example 1 (1) At 86°C, epoxy resin E-51, 4-hydroxycrotonic acid, N,N-diethylbenzylamine, p-hydroxyanisole, and anhydrous ethanol were reacted at a mass ratio of 1:0.9:0.006:0.0005:0.06 at 150 rpm for 40 min, then cooled to 30°C, phosphorus pentoxide (0.6 times the mass of epoxy resin E-51) was added, and distilled at 72°C and 200 rpm for 2 h to obtain a modified epoxy resin; (2) 3-chloropropyltriethoxysilane, diethoxydichlorosilane, decamethylcyclopentasiloxane, 2,4,6,8,10-cyclopentasiloxane, toluene, and zeolite molecular sieve were mixed in a mass ratio of 1:0.3:0.4:0.5:13:0.001, stirred evenly, placed in a 67°C oil bath, and added with an ethanol aqueous solution 4 times the mass of 3-chloropropyltriethoxysilane, wherein the mass ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution was 1:1. After reacting for 2 hours, tetramethyldihydrodisiloxane and 1,1,1-triethyl-3,3-dimethyldisiloxane were added in a mass ratio of 1:0.6, wherein the mass ratio of tetramethyldihydrodisiloxane to 3-chloropropyltriethoxysilane was 0.2:1. After reacting for 1.5 hours, the mixture was filtered, separated into layers, distilled at 143°C and 400 mmHg for 4 hours, and then baked at 190°C for 20 minutes to obtain a resin matrix; (3) The resin matrix was heated to 89°C, and modified epoxy resin, KP220, and ethyl acetate were added in a mass ratio of 1:0.0007:7. The mass ratio of modified epoxy resin to resin matrix was 0.4:1. After stirring at 150 rpm for 1 hour, the mixture was reacted for 9 hours under a nitrogen atmosphere, and then cooled to 20°C. 0.9 times the mass of n-propanol as the resin matrix was added. After reacting for 5 hours, the mixture was washed with deionized water until the solution pH was 6, and then distilled at 300 rpm and 77°C for 3 hours to obtain a homemade silicone resin. (4) placing the carbon nanotubes in 68% nitric acid with a mass fraction of 25 times the mass of the carbon nanotubes, ultrasonically treating at 25 kHz for 24 min, stirring at 60 rpm for 3 h, adding deionized water until the solution pH is 6, filtering, and drying at 68 °C for 6 h to obtain pretreated carbon nanotubes; (5) The pretreated carbon nanotubes were placed in deionized water with a mass of 180 times that of the pretreated carbon nanotubes. After 25kHz ultrasound for 10 minutes, cerium nitrate hexahydrate, sodium sulfate, and hexamethylenetetramine were added in a mass ratio of 1:0.08:0.1. The mass ratio of cerium nitrate hexahydrate to pretreated carbon nanotubes was 0.7:1. Under nitrogen protection, the oil bath was heated to 95°C. After stirring at 100 rpm for 16 hours, the mixture was filtered, rinsed with deionized water and anhydrous ethanol for 3 minutes, and dried at 60°C for 8 hours to obtain composite carbon nanotubes. (6) The composite carbon nanotubes were placed in butyl titanate with a mass 5 times that of the composite carbon nanotubes, subjected to 25kHz ultrasound for 4 hours, reacted at 200°C for 18 hours, heated to 600°C, kept at this temperature for 5 hours, cooled to 322°C, kept at this temperature for 6 hours, filtered, washed with deionized water for 6 times, and dried at 60°C for 3 hours to obtain the homemade filler; (7) The homemade silicone resin and homemade filler were mixed in a mass ratio of 1:1, stirred at 200 rpm for 3 h, and then 0.006 times the mass of the homemade silicone resin diluent 660A was added. The mixture was heated to 46 °C in a water bath, and hydrogen and nitrogen were introduced in a flow ratio of 3:1. The total flow rate of hydrogen and nitrogen was 150 mm 3 / s, raise the temperature to 220℃, keep it warm for 7h under vacuum of 300Pa, add 0.01 times the mass of homemade silicone resin triethylenetetramine and 0.002 times the mass of homemade silicone resin DMP-30, stir evenly, and obtain super wear-resistant and high hardness nano titanium ceramic coating.

[0021] Example 2 (1) At 91°C, epoxy resin E-51, 4-hydroxycrotonic acid, N,N-diethylbenzylamine, p-hydroxyanisole, and anhydrous ethanol were reacted at a mass ratio of 1:1.1:0.09:0.0008:0.18 at 200 rpm for 53 min, then cooled to 35°C, phosphorus pentoxide (0.8 times the mass of epoxy resin E-51) was added, and distilled at 81°C and 250 rpm for 3.5 h to obtain a modified epoxy resin; (2) 3-chloropropyltriethoxysilane, diethoxydichlorosilane, decamethylcyclopentasiloxane, 2,4,6,8,10-cyclopentasiloxane, toluene and zeolite molecular sieve were mixed in a mass ratio of 1:0.55:0.55:0.75:17.5:0.002, stirred evenly, placed in a 71°C oil bath, and an ethanol aqueous solution with a mass of 7.5 times that of 3-chloropropyltriethoxysilane was added. Anhydrous ethanol and deionized water in the ethanol aqueous solution were removed. The mass ratio of tetramethyldihydrogen disiloxane and 1,1,1-triethyl-3,3-dimethyldisiloxane was 1:1 after reaction for 3.5 hours, and the mass ratio of tetramethyldihydrogen disiloxane and 3-chloropropyltriethoxysilane was 0.4:1. After reaction for 2.3 hours, the mixture was filtered, separated and distilled at 148°C and 450mmHg for 6.5 hours, and then baked at 205°C for 28 minutes to obtain a resin matrix. (3) The resin matrix was heated to 92°C, and modified epoxy resin, KP220, and ethyl acetate were added in a mass ratio of 1:0.0009:11.5. The mass ratio of modified epoxy resin to resin matrix was 0.6:1. After stirring at 175 rpm for 2 h, the mixture was reacted for 13.5 h under a nitrogen atmosphere, cooled to 25°C, and n-propanol (1.4 times the mass of the resin matrix) was added. After reacting for 7.5 h, the mixture was washed with deionized water until the solution pH was 6.5, and distilled at 350 rpm and 81°C for 4.5 h to obtain a homemade silicone resin. (4) placing the carbon nanotubes in 68% nitric acid at a mass fraction of 30.5 times the mass of the carbon nanotubes, ultrasonically treating at 30 kHz for 30 min, stirring at 70 rpm for 5 h, adding deionized water until the solution pH is 6.5, filtering, and drying at 74 °C for 8.5 h to obtain pretreated carbon nanotubes; (5) The pretreated carbon nanotubes were placed in deionized water with a mass of 215 times that of the pretreated carbon nanotubes. After 30kHz ultrasound for 18 minutes, cerium nitrate hexahydrate, sodium sulfate, and hexamethylenetetramine were added in a mass ratio of 1:0.14:0.15, and the mass ratio of cerium nitrate hexahydrate to pretreated carbon nanotubes was 0.8:1. Under nitrogen protection, the oil bath was heated to 101°C, stirred at 115 rpm for 19 hours, filtered, rinsed with deionized water and anhydrous ethanol for 5 minutes, and dried at 65°C for 10 hours to obtain composite carbon nanotubes. (6) The composite carbon nanotubes were placed in butyl titanate (6.5 times the mass of the composite carbon nanotubes), subjected to 30kHz ultrasound for 5.5 hours, reacted at 210°C for 20 hours, then heated to 615°C, kept warm for 6.5 hours, cooled to 344°C, kept warm for 7.5 hours, filtered, washed with deionized water for 7 times, and dried at 65°C for 4 hours to obtain the homemade filler; (7) The homemade silicone resin and homemade filler were mixed in a mass ratio of 1:1.2, stirred at 250 rpm for 5 h, and then 0.008 times the mass of the homemade silicone resin diluent 660A was added. The mixture was heated to 52 °C in a water bath, and hydrogen and nitrogen were introduced in a flow ratio of 3:1. The total flow rate of hydrogen and nitrogen was 150 mm 3 / s, raise the temperature to 231°C, keep warm for 9.5h under a vacuum of 50Pa, add 0.02 times the mass of self-made silicone resin triethylenetetramine and 0.0035 times the mass of self-made silicone resin DMP-30, stir evenly, and obtain an ultra-wear-resistant and high-hardness nano titanium ceramic coating.

[0022] Example 3 (1) At 96°C, epoxy resin E-51, 4-hydroxycrotonic acid, N,N-diethylbenzylamine, p-hydroxyanisole, and anhydrous ethanol were reacted at a mass ratio of 1:1.4:0.01:0.001:0.3 at 250 rpm for 66 min, then cooled to 40°C, phosphorus pentoxide (1 times the mass of epoxy resin E-51) was added, and distilled at 89°C and 300 rpm for 5 h to obtain a modified epoxy resin; (2) 3-chloropropyltriethoxysilane, diethoxydichlorosilane, decamethylcyclopentasiloxane, 2,4,6,8,10-cyclopentasiloxane, toluene, and zeolite molecular sieve were mixed in a mass ratio of 1:0.8:0.7:1:22:0.003, stirred evenly, placed in a 75°C oil bath, and added with an ethanol aqueous solution 11 times the mass of 3-chloropropyltriethoxysilane, wherein the mass ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution was 1:1. After reacting for 5 hours, tetramethyldihydrodisiloxane and 1,1,1-triethyl-3,3-dimethyldisiloxane were added in a mass ratio of 1:1.4, wherein the mass ratio of tetramethyldihydrodisiloxane to 3-chloropropyltriethoxysilane was 0.6:1. After reacting for 3 hours, the mixture was filtered, separated into layers, distilled at 153°C and 500 mmHg for 9 hours, and then baked at 220°C for 36 minutes to obtain a resin matrix; (3) The resin matrix was heated to 95°C, and modified epoxy resin, KP220, and ethyl acetate were added in a mass ratio of 1:0.001:16. The mass ratio of modified epoxy resin to resin matrix was 0.8:1. After stirring at 200 rpm for 3 h, the mixture was reacted for 18 h under a nitrogen atmosphere. The mixture was cooled to 30°C, and n-propanol twice the mass of the resin matrix was added. After reacting for 10 h, the mixture was washed with deionized water until the solution pH was 7. The mixture was distilled at 400 rpm and 85°C for 6 h to obtain a self-made silicone resin. (4) placing the carbon nanotubes in 68% nitric acid at a mass fraction of 36 times the mass of the carbon nanotubes, ultrasonically treating at 35kHz for 36 minutes, stirring at 80rpm for 7 hours, adding deionized water until the solution has a pH of 7, filtering, and drying at 80°C for 11 hours to obtain pretreated carbon nanotubes; (5) The pretreated carbon nanotubes were placed in deionized water with a mass of 250 times that of the pretreated carbon nanotubes. After 35kHz ultrasound for 26 minutes, cerium nitrate hexahydrate, sodium sulfate, and hexamethylenetetramine were added in a mass ratio of 1:0.2:0.2, and the mass ratio of cerium nitrate hexahydrate to pretreated carbon nanotubes was 0.9:1. Under nitrogen protection, the oil bath was heated to 108°C, stirred at 130 rpm for 22 hours, filtered, rinsed with deionized water and anhydrous ethanol for 7 minutes, and dried at 70°C for 12 hours to obtain composite carbon nanotubes. (6) The composite carbon nanotubes were placed in butyl titanate with a mass 8 times that of the composite carbon nanotubes, subjected to 35kHz ultrasound for 7 hours, reacted at 220°C for 22 hours, heated to 630°C, kept at this temperature for 8 hours, cooled to 367°C, kept at this temperature for 9 hours, filtered, washed with deionized water for 8 times, and dried at 70°C for 5 hours to obtain the homemade filler; (7) The homemade silicone resin and homemade filler were mixed in a mass ratio of 1:1.5, stirred at 300 rpm for 7 h, and then 0.01 times the mass of the homemade silicone resin diluent 660A was added. The mixture was heated to 59 °C in a water bath, and hydrogen and nitrogen were introduced at a flow ratio of 3:1. The total flow rate of hydrogen and nitrogen was 150 mm 3 / s, raise the temperature to 242°C, keep warm for 12 hours under a vacuum of 70Pa, add 0.03 times the mass of the homemade silicone resin triethylenetetramine and 0.005 times the mass of the homemade silicone resin DMP-30, stir evenly, and obtain an ultra-wear-resistant and high-hardness nano titanium ceramic coating.

[0023] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that step (1) is omitted, and step (3) is changed to: at 25° C., a resin matrix is ​​placed in a container, 1.4 times the mass of n-propanol of the resin matrix is ​​added, reacted for 7.5 hours, washed with deionized water until the solution pH is 6.5, and distilled at 350 rpm and 81° C. for 4.5 hours to obtain a self-made silicone resin. The remaining preparation steps are the same as those of Example 2.

[0024] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that there is no step (2), and step (3) is changed to: the polymethyl silicone resin is heated to 92°C, and modified epoxy resin, KP220, and ethyl acetate are added in a mass ratio of 1:0.0009:11.5, and the mass ratio of modified epoxy resin to polymethyl silicone resin is 0.6:1, and stirred at 175rpm for 2h, reacted under nitrogen atmosphere for 13.5h, cooled to 25°C, and n-propanol 1.4 times the mass of polymethyl silicone resin was added, reacted for 7.5h, washed with deionized water until the solution pH was 6.5, and distilled at 350rpm and 81°C for 4.5h to obtain a self-made silicone resin. The remaining preparation steps are the same as those in Example 2.

[0025] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that step (3) is different. Step (3) is changed to: the resin matrix is ​​heated to 92°C, and modified epoxy resin, KP220, and ethyl acetate are added in a mass ratio of 1:0.0009:11.5, and the mass ratio of modified epoxy resin to resin matrix is ​​0.6:1. After stirring at 175 rpm for 2 hours, reacting for 13.5 hours under nitrogen atmosphere, distilling at 350 rpm and 81°C for 4.5 hours to obtain a self-made silicone resin. The remaining preparation steps are the same as those in Example 2.

[0026] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that there is no step (5), and step (6) is changed to: the pretreated carbon nanotubes are placed in butyl titanate with a mass 6.5 times that of the composite carbon nanotubes, after 30kHz ultrasound for 5.5 hours, react at 210°C for 20 hours, heat to 615°C, keep the temperature for 6.5 hours, cool to 344°C, keep the temperature for 7.5 hours, filter by suction, wash with deionized water for 7 times, and dry at 65°C for 4 hours to obtain the self-made filler. The remaining preparation steps are the same as those in Example 2.

[0027] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that there is no step (6), and step (5) is changed to: the pretreated carbon nanotubes are placed in deionized water with a mass of 215 times that of the pretreated carbon nanotubes, and after 30kHz ultrasound for 18 minutes, cerium nitrate hexahydrate, sodium sulfate, and hexamethylenetetramine are added in a mass ratio of 1:0.14:0.15, and the mass ratio of cerium nitrate hexahydrate to pretreated carbon nanotubes is 0.8:1. Under nitrogen protection, the oil bath is heated to 101°C, stirred at 115 rpm for 19 hours, and then filtered, rinsed with deionized water and anhydrous ethanol for 5 minutes in turn, and dried at 65°C for 10 hours to obtain the homemade filler. The remaining preparation steps are the same as those in Example 2.

[0028] Comparative Example 6 The difference between Comparative Example 6 and Example 2 is that step (7) is different. Step (7) is changed to: the homemade silicone resin and the homemade filler are mixed in a mass ratio of 1:1.2, stirred at 250 rpm for 5 hours, and then 0.008 times the mass of the homemade silicone resin diluent 660A, 0.02 times the mass of the homemade silicone resin triethylenetetramine, and 0.0035 times the mass of the homemade silicone resin DMP-30 are added, and stirred evenly to obtain an ultra-wear-resistant and high-hardness nano titanium ceramic coating. The remaining preparation steps are the same as those in Example 2.

[0029] Effect example Table 1 below shows the performance analysis results of the ultra-wear-resistant and high-hardness nano titanium ceramic coatings of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0030] Table 1 Wear amount (g) Adhesion grade Example 1 0.011 Level 1 Example 2 0.010 Level 1 Example 3 0.012 Level 1 Comparative Example 1 0.015 Level 4 Comparative Example 2 0.012 Level 3 Comparative Example 3 0.11 Level 3 Comparative Example 4 1.15 Level 1 Comparative Example 5 0.99 Level 1 Comparative Example 6 0.25 Level 1 From the comparison of the wear amount experimental data of the embodiment and the comparative example, it can be found that the acidified carbon nanotubes can adsorb cerium ions, precipitate as nucleation points, grow to form layered rare earth hydroxides, and then intercalate butyl titanate, and heat twice to form titanium porcelain. The carbon nanotubes, layered rare earth hydroxides and titanium porcelain are interlocked with each other to form a three-dimensional composite structure, which is tightly stacked and plays the role of a wear-resistant skeleton. In addition, the homemade silicone resin and the homemade filler are connected with silicon oxygen bonds to improve the density. Then, through ion nitriding treatment, while the grains are refined, a lubricating layer is formed on the surface of the homemade filler, which effectively improves the wear resistance of the coating. From the comparison of the adhesion level experimental data of the embodiment and the comparative example, it can be found that the present invention uses 4-hydroxycrotonic acid and phosphorus pentoxide to modify the epoxy resin, and then reacts with the resin matrix. The high viscosity of the epoxy resin can improve the peeling resistance of the coating, and the phosphate group can form a strong chelating effect with the surface of the metal substrate, thereby increasing the peeling resistance of the coating. Then, the resin matrix is ​​further modified with n-propanol, which can be bridged with the surface of the metal substrate by silane bonds to improve the peeling resistance of the coating.

[0031] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a super wear-resistant and high-hardness nano titanium ceramic coating, characterized in that: The method comprises the following preparation steps: (1) At 91°C, epoxy resin E-51, 4-hydroxycrotonic acid, N,N-diethylbenzylamine, p-hydroxyanisole, and anhydrous ethanol were reacted at a mass ratio of 1:1.1:0.09:0.0008:0.18 at 200 rpm for 53 min, then cooled to 35°C, phosphorus pentoxide (0.8 times the mass of epoxy resin E-51) was added, and distilled at 81°C and 250 rpm for 3.5 h to obtain a modified epoxy resin; (2) 3-chloropropyltriethoxysilane, diethoxydichlorosilane, decamethylcyclopentasiloxane, 2,4,6,8,10-cyclopentasiloxane, toluene and zeolite molecular sieve were mixed in a mass ratio of 1:0.55:0.55:0.75:17.5:0.002, stirred evenly, placed in a 71°C oil bath, and an ethanol aqueous solution with a mass of 7.5 times that of 3-chloropropyltriethoxysilane was added. Anhydrous ethanol and deionized water in the ethanol aqueous solution were removed. The mass ratio of tetramethyldihydrogen disiloxane and 1,1,1-triethyl-3,3-dimethyldisiloxane was 1:1 after reaction for 3.5 hours, and the mass ratio of tetramethyldihydrogen disiloxane and 3-chloropropyltriethoxysilane was 0.4:

1. After reaction for 2.3 hours, the mixture was filtered, separated and distilled at 148°C and 450mmHg for 6.5 hours, and then baked at 205°C for 28 minutes to obtain a resin matrix. (3) The resin matrix was heated to 92°C, and modified epoxy resin, KP220, and ethyl acetate were added in a mass ratio of 1:0.0009:11.

5. The mass ratio of modified epoxy resin to resin matrix was 0.6:

1. After stirring at 175 rpm for 2 h, the mixture was reacted for 13.5 h under a nitrogen atmosphere, cooled to 25°C, and n-propanol (1.4 times the mass of the resin matrix) was added. After reacting for 7.5 h, the mixture was washed with deionized water until the solution pH was 6.5, and distilled at 350 rpm and 81°C for 4.5 h to obtain a homemade silicone resin. (4) placing the carbon nanotubes in 68% nitric acid at a mass fraction of 30.5 times the mass of the carbon nanotubes, ultrasonically treating at 30 kHz for 30 min, stirring at 70 rpm for 5 h, adding deionized water until the solution pH is 6.5, filtering, and drying at 74 °C for 8.5 h to obtain pretreated carbon nanotubes; (5) The pretreated carbon nanotubes were placed in deionized water with a mass of 215 times that of the pretreated carbon nanotubes. After 30kHz ultrasound for 18 minutes, cerium nitrate hexahydrate, sodium sulfate, and hexamethylenetetramine were added in a mass ratio of 1:0.14:0.15, and the mass ratio of cerium nitrate hexahydrate to pretreated carbon nanotubes was 0.8:

1. Under nitrogen protection, the oil bath was heated to 101°C, stirred at 115 rpm for 19 hours, filtered, rinsed with deionized water and anhydrous ethanol for 5 minutes, and dried at 65°C for 10 hours to obtain composite carbon nanotubes. (6) The composite carbon nanotubes were placed in butyl titanate (6.5 times the mass of the composite carbon nanotubes), subjected to 30kHz ultrasound for 5.5 hours, reacted at 210°C for 20 hours, then heated to 615°C, kept warm for 6.5 hours, cooled to 344°C, kept warm for 7.5 hours, filtered, washed with deionized water for 7 times, and dried at 65°C for 4 hours to obtain the homemade filler; (7) The homemade silicone resin and homemade filler were mixed in a mass ratio of 1:1.2, stirred at 250 rpm for 5 h, and then 0.008 times the mass of the homemade silicone resin diluent 660A was added. The mixture was heated to 52 °C in a water bath, and hydrogen and nitrogen were introduced in a flow ratio of 3:

1. The total flow rate of hydrogen and nitrogen was 150 mm 3 / s, raise the temperature to 231°C, keep warm for 9.5h under a vacuum of 50Pa, add 0.02 times the mass of self-made silicone resin triethylenetetramine and 0.0035 times the mass of self-made silicone resin DMP-30, stir evenly, and obtain an ultra-wear-resistant and high-hardness nano titanium ceramic coating.